The Major Mechanisms for Efficient Hybrid Energy Harvesting: Overview and Recent Developments - Obilikpa, Stanley; Onochie, Uche; Nweze, Chinyere; Nwoziri, Chinomso; Kalu, Bright; Anazodo, Ken-Basil; Nweke, Chima (Asian Review of Mechanical Engineering, 2021)
Devastating environmental issues and the cost of replacement of batteries in autonomous low-powered electrical, electronic, and mechatronic systems, the interest in ambient energy harvesting has witnessed steady growth recently. The maximization and utilization of these eco-friendly energies have given rise to efficient hybrid energy harvesting, which involves the combination of two or more standalone energy harvesting mechanisms such as Vibrational, thermoelectric, pyroelectric, photovoltaic, etc. The comparison of the recent development, applications, and challenges of the major standalone and hybrid harvesting mechanisms in both large and small-scale mechanisms are the main emphasis of this article. Also, this review holistically discussed the latest optimal techniques utilized in hybrid energy harvesting mechanisms for the effective performance of systems and to guarantee stable power to autonomous electronics and wireless sensor networks. The study will help research scholars to understand and focus on the high-potential techniques to achieve maximum power from hybrid harvesters.